Penerapan Standar Proses Sebagai Wujud Visi Misi Madrasah Ibtidaiyah Swasta Hikmatul Salridho - Harahap, Alwi Shihab Syah; Chaniago, Nasrul Syakur; B, Budi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The research that has been carried out is entitled "Implementation of Educational Process Standards as a Manifestation of the Vision and Mission of MIS Hikmatul Salridho" which is based on the discrepancy between policies made by the central government and their implementation at the madrasah level. This is caused by several factors, including a lack of resources, be it competent teachers, adequate facilities, or sufficient budget. Teachers at MIS Hikmatul Salridho and the head and deputy head of the madrasah for curriculum serve as information sources for this qualitative research technique. Three methods are employed to gather data: documentation, interviews, and observation. The present study employs data reduction, data presentation, and conclusion drafting as data analysis approaches. The research results revealed that (1) The availability of facilities and infrastructure at MIS Hikmatul Salridho was sufficient to accommodate all the existing romber, namely 11 romber. The facilities in each classroom are considered good enough to carry out the learning process. (2) The implementation of the learning process at MIS Hikmatul Salridho consists of planning, implementation and assessment stages. In its implementation, based on observations made, it was not fully implemented according to the RPP and lacking in classroom management, (3) The effectiveness of the learning process can be seen from student participation in learning and participation is not evenly carried out by students. Based on the research results above, the implementation of process standards must be managed well, apart from that, the head of the madrasah together with the Curriculum WKM must always carry out monitoring, and teachers should carry out learning in a structured manner to achieve learning goals.